How does Open Source Software contribute to socio-economic development? An investigation of Open Source Software as an alternative approach to technology diffusion, adoption and adaptation for health information systems development and socio-economic impact in Mozambique - Emdon, Heloise (My University, 2010)
Abstract Developing countries are net importers of intellectual property products and open source software (OSS) production is one way in which local socio-economic development can take place. The public goods characteristics of OSS are contested and this study investigates whether in a developing country context OSS is a pure public good that can be locally appropriated and not exclude any users or producers from doing so. This case study of an OSS public good finds that it does not have all the characteristics of a pure good, that there is a role for a sponsor, and in particular the importance of copyright protection of derivatives in order to ensure that the source code does not fall out of fashion and use. Having explored that, however, there is further evidence that OSS collaborative learning is both publically and personally beneficial for developing country computer programmers. Furthermore, the state benefits from the improved benefits of health information systems made possible through the appropriation of this model of learning.
Keywords: Open Source Software; socio-economic development; public goods; intellectual property rights; copyright; capacity building; health information system; health governance; public service delivery; Mozambique; South Africa